A creator's guide to transmedia storytelling how to captivate and engage audiences across multiple platforms - Phillips, Andrea 1974- (New York McGraw-Hill, 2012)
This is the first major, comprehensive resource to feature concrete instruction on the principles of storytelling, audience engagement, platform selection, execution challenges, big-picture strategy and structural considerations -- as well as case studies of milestone transmedia projects and interviews with leading transmedia authorities and creators. Whether you're in game design and development, book publishing, film and television, or any other traditional or digital medium, A Creator's Guide to Transmedia Storytelling will give you the tools and knowledge you need to create deeper forms of audience engagement.
Section I. Introduction to transmedia : Once upon a time ; What is transmedia, anyway? ; Transmedia is more than a marketing gimmick ; Significant prior art to learn from -- Section II. Storytelling : The four creative purposes for transmedia storytelling ; Learn the basics of traditional storytelling ; How story and branding affect marketing ; Writing for transmedia is different ; Online, everything is characterization ; Conveying action across multiple media -- Section III. Structure : Fine-tuning for depth or for scale (not both) ; Special considerations for blockbuster transmedia franchises ; Interactivity creates deeper engagement ; Uses and misuses for user-generated content ; Challenging the audience to act ; Make your audience a character, too -- Section IV. Production : Project management: the unsung necessity ; Finding and keeping a strong core team ; Websites and tech development : DIY or outsourcing?n ; Don't be a jerk on social media ; Email and phone: cheap and effective ; Making and using prerecorded content ; Brining your story into the real world -- Section V. The big picture : How to fund production costs ; And maybe make some profit, too ; Forging your own transmedia career ; Critical legal and ethical considerations ; Get excited and make things.
Includes bibliographical references and index.
Keywords: Digital storytelling; Interactive multimedia; Internet entertainment industry; Marketing -- Psychological aspects